IMOBILIZAÇÃO DE COMPLEXO DE RUTÊNIO CONTENDO BASE DE SCHIFF NA UNIDADE METALOORGÂNICA UiO-67 - Herculys B. Jorge; Cleiser T. P. da Silva; Helena S. Nakatani; Andrelson W. Rinaldi; Vagner R. De Souza (Química Nova)
Zirconium-based metal-organic framework, UiO-67, was synthesized and used as support for the immobilization of the [RuCl2(ENAPY)] (ENAPY = N,N'-bis(7-metyl-2-pyridylmethylene)-1,2-diiminoethane)). The immobilized system exhibited violet-blue color. The {UiO-67/[RuCl2(ENAPY)]} was characterized by cyclic voltammetry, X-ray diffraction, UV-Vis, FTIR and X-ray photoelectron spectroscopy. The electrochemistry of the immobilized system is characterized by a reversible pair of waves at +0.40 V (vs NHE), ascribed to the Ru3+/2+ redox process. The electronic spectrum of the immobilized system is characterized by bands at 520 and 380 nm ascribed to a ligand-to-metal charge-transfer transitions {Ru2+(dπ) → ENAPY(pπ*)}. The IR bands of immobilized complex {1630 cm-1 (νasC=C), 1590 cm-1 (νasC=N), 1450 cm-1 (νsC=C), 1340 cm-1 (νsC=C)} are weak in comparison with the neat complex due to their low concentration in MOF cages. X-ray diffractogram of the immobilized system indicated that the crystallinity and morphology of UiO-67 was preserved during inclusion of ruthenium complex. The XPS spectra of UiO-67 and UiO-67/ruthenium complex shows a signal at 462 eV that can be ascribed to Ru 3p3/2 and at 400 eV ascribed to N 1s core level of the ruthenium Schiff base complex immobilized into MOF.